1997
DOI: 10.1021/js960399i
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Infusion of Lidocaine on Its Pharmacokinetics in Conscious Instrumented Dogs

Abstract: In this study, potential alterations in hepatic blood flow, plasma protein binding, hepatic tissue binding, and enzyme activities induced by LD iv infusion of lidocaine (LD) were evaluated using a chronically instrumented dog model. Four conscious female mongrel dogs (19.0-23.5 kg) were each given, on days 1 and 10, a 5-min infusion of a mixture of unlabeled LD at approximately 2 mg/kg and 14C-labeled LD at approximately 25 microCi and, on day 8, a 12-h constant rate iv infusion of LD (approximately 76 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The second N‐de‐ethylation step produces GX, which is eliminated more slowly, may potentiate lidocaine‐induced seizures and lacks anti‐arrhythmic activity. The plasma concentrations of GX start accumulating after 4 hours at an infusion rate of 76 μg kg −1 minute −1 in conscious dogs, while lidocaine and MEGX do not appear to accumulate (Ngo Ly et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second N‐de‐ethylation step produces GX, which is eliminated more slowly, may potentiate lidocaine‐induced seizures and lacks anti‐arrhythmic activity. The plasma concentrations of GX start accumulating after 4 hours at an infusion rate of 76 μg kg −1 minute −1 in conscious dogs, while lidocaine and MEGX do not appear to accumulate (Ngo Ly et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Emesis was observed at plasma lidocaine concentrations greater than 4 μg mL −1 in our study. Nausea and emesis have been reported in conscious dogs receiving 76 μg kg −1 minute −1 for 12 hours (Ngo Ly et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This precluded the estimation of the disposition pharmacokinetic parameters CL and V, of its terminal elimination rate, and of the absolute bioavailability F. But using one or more i.v. study arms in the same dogs may decrease the intrinsic clearance of lidocaine [35], and therefore hinder the elucidation of the effects of adrenaline on its absorption kinetics. Still, the disposition pharmacokinetic parameters estimated in this study are comparable to those of previous studies: one reported a CL of 0.04 L·min -1 ·kg -1 and a V of 1.44 L·kg -1 after a lidocaine i.v.…”
Section: Discussionmentioning
confidence: 99%
“…, 1996; Orszulak‐Michalak et al. , 2002), dogs (Difazio & Brown, 1972; Ngo et al. , 1997), sheep (Mather et al.…”
Section: Plasma Pharmacokinetic Parameters Of Intravenously Administmentioning
confidence: 99%